99.6k views
0 votes
-4 2/6 / 1 2/3. please help me solve this!

User Nolanpro
by
5.3k points

2 Answers

3 votes
hbkjjjnjhrjfjrjjrjfjejehehehehe
User Diego Antunes
by
5.8k points
0 votes

- 2
(3)/(5)

note that
(2)/(6) =
(1)/(3)

require - 4
(1)/(3) ÷ 1
(2)/(3)

change mixed numbers to improper fractions

= -
(13)/(3) ÷
(5)/(3)

change ÷ to × and turn second fraction upside down

=-
(13)/(3) ×
(3)/(5) ← ( cancel the 3's )

= -
(13)/(5) = - 2
(3)/(5)


User MrKos
by
4.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.